Des origines indo-européennes de shall - Dennis Philps (Anglophonia)
This paper presents the hypothesis that *(s)kel- ’to owe, be under an obligation’ continued in Old English by sculan and in Modern English by shall, is derived by a process of grammaticalisation and subsequent lexicalisation from homonymic PIE *(s)kel-’to cut’, via a putative specialized meaning of the latter, namely ’to cut notches on a tally stick to symbolize a duty, a debt, an obligation’. On a linguistic level, this hypothesis is based on the assumption that the IndoEuropean perfect denotes a state resulting from the completion of an earlier event. On a non linguistic level, it is accredited by the fact that the oldest Germanic civilizations symbolized relations of obligation by cutting notches on a tally stick.